The effects of paternalistic leadership on task performance: Testing a moderated mediation model in Turkish organizations - ERDİLEK KARABAY, MELİSA (NOMOS VERLAGSGESELLSCHAFT MBH & CO KG, 2021)
Drawing on the findings from a serial moderated mediation model, this study aims to expand prior research by investigating the interaction between paternalist leadership and employee task performance. Study also aims to test the indirect effects of perceived person-organization fit and psychological ownership on the relationship between paternalistic leadership and employee task performance, through serial mediation models. Furthermore, the moderating role of organizational size in direct and all indirect relations between paternalistic leadership and task performance, through five different models is tested. Sample consists of 1,652 employees from various industries in Istanbul, Turkey. Hypothesized relationships were tested through structural equation modelling. The findings demonstrated the significant positive direct relationship between paternalistic leadership and employee task performance. Psychological ownership mediated the relationship of paternalistic leadership and task performance while person-organization fit had no mediating effect. Practical implications and further recommendations are also discussed.
Keywords: Paternalistic leadership; Person-organization fit; Psychological ownership; Task performance; Organizational size; SOCIAL IDENTITY THEORY; PSYCHOLOGICAL OWNERSHIP; PERSON-ORGANIZATION; TRANSFORMATIONAL LEADERSHIP; JOB-SATISFACTION; MEMBER EXCHANGE; CHARISMATIC LEADERSHIP; CONTEXTUAL PERFORMANCE; SELF-CATEGORIZATION; VALUE CONGRUENCE